Uso do Laser ALGaInP na cicatrização de lesões cutâneas experimentais em coelhos - Beheregaray, Wanessa Krüger; Gianotti, Giordano Cabral; Leal, Juliano de Souza; Monteiro, Fabíola de Moares; Simas, Silvana Mello; Elizeire, Mariane; Contesini, Emerson Antonio (Acta Scientiae Veterinariae, 2018)
Background : : : : Animals with extensive cutaneous lesions remain hospitalized for long periods. In addition to increasing treatment costs, this also causes stress in these animals. Low-power laser is widely used to support tissue repair processes. Its use in the treatment of cutaneous wounds has been studied, as it reduces the wound healing period and the consequences caused by the lesion. The study aimed to evaluat the wound healing process of experimental cutaneous wounds in rabbits with the use of laser therapy. Materials, Methods & Results: Ten healthy New Zealand rabbits were used in the study, which were divided in two groups (n=5). Skin biopsies were carried out on day 16 in Group 1 and on day 8 in Group 2. The animals were under general anesthesia for the experimental cutaneous lesion to be carried out. Two 1cm2 wounds were made on the back of each animal. The lesions were measured by a pachymeter in the immediate postoperative period, then covered with sterile gauze and maintained with rubber bandages. The animals were treated only with Tramadon 3 mg.kg-1 twice a day, during 3 days. Only the lesions on the right side of the animals were irradiated regularly, on each side of the wound, at a distance of 0.5 cm from the margin. The equipment used was a 660nm wavelength AlGaInP laser diode (Laserpulse, Ibramed), pulsed at a frequency of 20 Hz, at a dose of 3J and stimulation time of 12s. The left-side lesions represented the control and the treatment administered to them consisted only of a cleanse using a NaCl solution at 0.9% once a day. The measurement of the lesion area was made every two days with a pachymeter, and the macroscopic characteristics were noted on a control card. For the histological evaluation of the wound healing process, biopsy specimens were taken from the right and left lesions on the sixteenth day in G1 and on the eighth day in G2, by means of a 6mm punch. The samples were stained with Hematoxylin-eosin for the global evaluation of the tissue section, and with Masson’s trichrome for evaluation of the presence of collagen fibers in interstitial fibrosis sites. Hyperemia followed by a discreet bleeding could be observed in wounds treated with laser after its application. With regard to the wound healing area, there was no difference between treated and control animals in both groups. However, in the microscopic evaluation of G1, in relation to the histological variables, significantly higher results were found in lesions treated with laser however, in the microscopic evaluation of G1, in relation to the histological variables, significantly higher results were found in lesions treated with laser: vascular proliferation, fibroblast and collagen proliferation, as well as the presence of hair follicles. In G2, only the fibroblastic proliferation showed a significant difference (p= 0.08) in lesions treated with laser. Discussion: There was no difference in the number of inflammatory cells in this study, perhaps because the control animals underwent laser treatment of the contralateral lesion. However, the treated animals had a higher number of deposited collagen fibers than the control ones, corroborating the data mentioned in literature. The most important result found was associated with vascular proliferation, which showed a significant difference (p= 0.046). The formation of new blood vessels seems to be substantially facilitated by the laser use, because a relatively higher number of elements was found in the group irradiated by it, as similarly hyperemia and bleeding were observed during treatment. The results obtained suggest that irradiation with AlGaInP diode laser, at a dose of 3J, acted as a biostimulative agent in the wound healing of experimental lesions. Evidence of this could be demonstrated by an accelerated cell proliferation process during the experiment. The experimental lesion, animal species selected and laser application method were adequate for the execution of this project.